Teaching leaders to lead teachers educational administration in the era of constant crisis - Donahoo, Saran; Hunter, Richard C., Dr (Advances in educational administration, 2007)
"Teaching Leaders to Lead Teachers: Educational Administration in the Era of Constant Crisis" - In the 21st century, the perceived crisis in how schools educate students significantly influences the decision of teachers to move into administrative positions as well as their ability to succeed once they take on these positions. Influenced by the media, the community and the teacher's lounge, many good educators are increasingly unwilling or simply unprepared to make the jump into school leadership and management. This book addresses some of the issues that affect school leadership by providing insights into the current state of educational administration in the hope of demystifying or dismissing some of the popular assumptions regarding what really takes place in the administration office. In doing so, this text examines topics related to the preparation and training of prospective administrators, factors that affect the process of leading in learning environments and perspectives on the state and structure of school leadership research and development.